Hubungan Motivasi Akademik dengan Prestasi Belajar Siswa SMA X di Jakarta Barat - Gunadi, Chintia Leo; Gunawan, William (Noetic Psychology, 2014)
AbstrakÃÂ ÃÂ Academic Motivation is an important factor for students. Having a good academic motivation will enhance student achievement. There were contradictory result on the relationship between academic motivation and student achievement. This research aims to explore the relation between academic motivation and student achievement. Using purposive sampling, 180 high school student in Jakarta area were chosen as subject. Academic motivation was measured using LOMOT (Lowo Academic Motivation) dimension of SMALSI (School Motivation and Learning Styles Inventory), while student achievement measured using school grade by the end of the semester. The result showed that there were a relationship (r=0,301; p<0,05) between academic motivation and academic achievement in high school student.Kata Kunci : academic motivation, academic achievement, high school student